2017
DOI: 10.22159/ajpcr.2017.v10i11.20918
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Chenopodium Quinoa Seed Against Ccl4-Induced Liver Toxicity in Swiss Albino Male Mice

Abstract: Objective:To study the effect of Quinoa seed on carbon tetrachloride (CCL 4 )-induced liver toxicity in Swiss albino male mice. Methods:Swiss albino male mice were divided into three groups: Group 1 served as control group; Group 2 served as hepatotoxic group (CCl 4 treated); and Group 3 served as combination of Quinoa seed powder (20 mg/kg) + CCl 4 -treated group. The effect of these groups on liver tissue was studied after three different periods of 4, 8, and 12 weeks. Liver marker enzyme level of serum glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…Supplementation with QU seed and PP peel at the level of 20% in the diet of the fish challenged with A. sobria showed a significant modulation in the activities of the enzymes AST, ALT, and ALP. This finding agrees with Saxena et al [86], who reported that treatment with QU seed powder significantly reduced the activities of CCl4-induced hepatic enzymes in Swiss albino mice (Mus musculus). Moreover, pretreatment with PP extract significantly reduced the levels of serum hepatic enzymes elevated upon lithium exposure in Wistar rats (Rattus norvegicus) [16].…”
Section: Discussionsupporting
confidence: 93%
“…Supplementation with QU seed and PP peel at the level of 20% in the diet of the fish challenged with A. sobria showed a significant modulation in the activities of the enzymes AST, ALT, and ALP. This finding agrees with Saxena et al [86], who reported that treatment with QU seed powder significantly reduced the activities of CCl4-induced hepatic enzymes in Swiss albino mice (Mus musculus). Moreover, pretreatment with PP extract significantly reduced the levels of serum hepatic enzymes elevated upon lithium exposure in Wistar rats (Rattus norvegicus) [16].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with Halaby et al [ 55 ] who indicated the attenuation effect of quinoa seeds on ALT (30%) and AST (40%) enzymes in rats with induced hypercholesterolemia. Similarly, Saxena et al [ 56 ] confirmed the effects of quinoa extracts on elevated serum ALT and AST enzymes in rats against CCl4-induced oxidative stress. The TBILI indicates the liver injury and CCl 4 had a significantly higher level than NR and treated groups (Si-Vit E, RQS, and YEQ).…”
Section: Discussionmentioning
confidence: 86%
“…A previous study indicated quinoa seed ( Chenopodium quinoa) showed a hepatoprotective effect against CCl 4 -induced liver damage. Chenopodium quinoa seed lowered CCl 4 -induced AST and ALT activities and liver damage by raising SOD and GSH levels [ 15 ]. However, the mechanisms associated with the protection against CCl 4 -induced inflammation and fibrosis were still unclear.…”
Section: Discussionmentioning
confidence: 99%